2018
DOI: 10.24908/ss.v16i2.6826
|View full text |Cite
|
Sign up to set email alerts
|

Cinema Censorship and Media Citizenship in the Hong Kong Film Ten Years

Abstract: Cinema censorship is a relatively unexplored topic in the discipline of surveillance studies. While movies are frequent references throughout the scholarship, such citations tend to be limited to plot and imagery and overlook the ways in which the medium can be subject to state intervention or other forms of censorship and self-censorship. This essay uses the case of the 2015 Hong Kong independent film Ten Years to explore how cinema deserves to be considered alongside other media and communications whose vuln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…Our finding is consistent with a previous study conducted in China, which found that the more one was exposed to news (e.g., through newspaper, television, or radio), the more one developed trust in government (Shen & Guo, 2013). Therefore, it makes sense that the same pattern was uncovered in Hong Kong, where traditional news sources are increasingly censored by the government, or self-censored (Chan & Lee, 2007;Fang, 2018;Weber & Fan, 2016). However, we also found that digital media use in Hong Kong was associated with more negative attitudes toward the government, the system, and the nation, which may reflect a widening split between the central government and the Hong Kong society.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our finding is consistent with a previous study conducted in China, which found that the more one was exposed to news (e.g., through newspaper, television, or radio), the more one developed trust in government (Shen & Guo, 2013). Therefore, it makes sense that the same pattern was uncovered in Hong Kong, where traditional news sources are increasingly censored by the government, or self-censored (Chan & Lee, 2007;Fang, 2018;Weber & Fan, 2016). However, we also found that digital media use in Hong Kong was associated with more negative attitudes toward the government, the system, and the nation, which may reflect a widening split between the central government and the Hong Kong society.…”
Section: Discussionsupporting
confidence: 91%
“…In the context of Hong Kong, after the Handover, the political relationship between Hong Kong and Beijing has become one of the largest influences on Hong Kong media (F. L. F. Chan & Lee, 2007). Hong Kong's traditional mass media (i.e., television news, newspaper, and radio) is suggested to be increasingly deferential to the political interests of Beijing and its corporate allies in Hong Kong (Frisch, Belair-Gagnon, & Agur, 2018) and were reportedly being censored by authorities (Fang, 2018;Kan, 2019;Weber & Fan, 2016). Such exposure to censored media predicts higher national identification and political trust (Shen & Guo, 2013).…”
Section: Media Use: Tools Working Alongside Living Historical Memoriesmentioning
confidence: 99%
“…However, they also face challenges posed by the censorship regime, especially since 2012, when the tightening of film censorship has made the dissemination of independent films more difficult. Thus, the topic of film censorship remains an underexplored area in independent film studies (Fang, 2018). Despite these challenges, independent documentaries have made significant contributions to civic culture, reflecting an aesthetic of observation that stimulates reflection and discussion (Troost, 2022).…”
Section: Background Of Studymentioning
confidence: 99%
“…Fang (2018) argues that some of the most prominent media to emerge in recent years have sought to not only highlight the growing tensions and anxieties within Hong Kong society at the growing encroachment of the Mainland, but also to draw parallels which are pertinent to those outside of Hong Kong. Increases in political participation among the local population, particularly as antagonism towards the Central government, led to a rise in a “localist” political sphere (Xia, 2016).…”
Section: Public Conceptualisations Of Citizenship In Hong Kongmentioning
confidence: 99%
“…Given that the protests in 2019 were largely seen as student-led movements, it follows that this will also have had a significant impact on how young people in Hong Kong conceptualise their sense of citizenship and identity related to the territory, although this remains to be seen. Fang (2018) argues that some of the most prominent media to emerge in recent years have sought to not only highlight the growing tensions and anxieties within Hong Kong society at the growing encroachment of the Mainland, but also to draw parallels which are pertinent to those outside of Hong Kong. Increases in political participation among the local population, particularly as antagonism towards the Central government, led to a rise in a "localist" political sphere (Xia, 2016).…”
Section: Public Conceptualisations Of Citizenship In Hong Kongmentioning
confidence: 99%